2012
DOI: 10.1007/s12028-012-9767-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased CSF Concentrations of Myelin Basic Protein After TBI in Infants and Children: Absence of Significant Effect of Therapeutic Hypothermia

Abstract: Background The objectives of this study were to determine effects of severe traumatic brain injury (TBI) on cerebrospinal fluid (CSF) concentrations of myelin basic protein (MBP) and to assess relationships between clinical variables and CSF MBP concentrations. Methods We measured serial CSF MBP concentrations in children enrolled in a randomized controlled trial evaluating therapeutic hypothermia (TH) after severe pediatric TBI. Control CSF was obtained from children evaluated, but found not to be having CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 29 publications
(55 reference statements)
1
40
0
1
Order By: Relevance
“…While serum and CSF were not analyzed in this study, RmTBI did affect expression of these markers in brain tissue in a similar manner. GFAP, MBP, NFL , and Tau have all been implicated in functional deficits after TBI and neurodegeneration,30, 33, 57, 58, 59, 60, 61, 62, 63, and therefore may be involved in the behavioral and MRI results observed in this study. For example, Budde et al, investigated DTI changes following blast TBI in rats and found reduced FA in the medial PFC at both four and 30 days postinjury, with rats exposed to high‐blast exhibiting a wider pattern of reduced FA compared to those exposed to low‐blast 52.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While serum and CSF were not analyzed in this study, RmTBI did affect expression of these markers in brain tissue in a similar manner. GFAP, MBP, NFL , and Tau have all been implicated in functional deficits after TBI and neurodegeneration,30, 33, 57, 58, 59, 60, 61, 62, 63, and therefore may be involved in the behavioral and MRI results observed in this study. For example, Budde et al, investigated DTI changes following blast TBI in rats and found reduced FA in the medial PFC at both four and 30 days postinjury, with rats exposed to high‐blast exhibiting a wider pattern of reduced FA compared to those exposed to low‐blast 52.…”
Section: Discussionmentioning
confidence: 66%
“…Of note, previous studies have investigated the abovementioned markers in TBI patients and found evidence for increases in NFL, 53, 54 GFAP ,55 and Tau 56 concentrations, as well as decreased MBP ,57 in cerebral spinal fluid and/or serum. While serum and CSF were not analyzed in this study, RmTBI did affect expression of these markers in brain tissue in a similar manner.…”
Section: Discussionmentioning
confidence: 95%
“…S100β and NSE are the marker molecules positioning in neurons, the former is a kind of calcium-binding protein, and it is closely related to the regulation of Ca2+ homeostasis within neurons and the regulation of cytoskeleton elements; the latter is the key enzyme of glycolysis function way in neurons, and it is of great significance to the neuron ATP production and function [17]. GFAP and MBP are the marker molecules positioning in the glial cells, and they are mainly involved in the regulation of glial cell structure stability and skeleton structure formation [18][19][20]. In order to define the recovery of neurological function in convalescence after acute cerebral hemorrhage, serum nerve injury-related molecule levels were analyzed in the study to reflect the degree of nerve damage, and then assess the recovery of neurological function.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that after the treatment at days 1, 3, 5 and 7 after treatment, the levels of ICP in patients of the ganglioside group were significantly lower than those of the normal treatment group, while the levels of P bt O 2 were significantly higher than those of the normal treatment group, which indicated that adjuvant therapy [23,24]. MBP is a kind of strong alkaline membrane protein of oligodendrocyte cell and scabbard film cells on the surface regulating and maintaining the cellular structure and stability of function [25]. NGB is a kind of globin located in the neurone delivering oxygen to brain tissue specifically [26,27].…”
Section: Discussionmentioning
confidence: 99%